EXPERIENCE OF ISOTOPE TECHNOLOGIES APPLICATION TO STUDY CHANGES IN DEEP-WATER POTABLE AQUIFERS STATE WITHIN KYIV IN CONDITIONS OF LONG-TERM OPERATION - Koshliakov О.; Koshliakova Т.; Dyniak О.; Koshliakova І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The presented research is devoted to study and establishment of the spatiotemporal change of tritium content in groundwater of CenomanianCallovian groundwater complex in Kyiv and the causes of these changes in order to identify water exchange features and hydraulic interaction between shallow and deep aquifers, as well as between groundwater and surface waters. Due to the excessive use of groundwater, depressive surfaces of hydrodynamic pressures have formed, aquifers are transforming from pressure head to pressureless, and there is a danger of downward filtration and contamination of potable groundwater. Also, one of the effects of these depressions formation is deterioration of water quality. However, to study the conditions of the qualitative composition formation of deep potable aquifers and to identify the causes of changes in groundwater status is a difficult and responsible task at the same time. Methods of isotopic hydrogeology are among the main scientific methods used to track the peculiarities of groundwater movement and assess their age. The new data obtained by isotopic methods help to control water resources and allow to make such decisions that will bring socio-economic benefits. The obtained data of tritium content in groundwater of Cenomanian-Callovian groundwater complex, clearly presented in the form of maps, allow to make informed decisions on sustainable resource management, and regular monitoring of chemical and isotopic composition of groundwater reveals mechanisms of recharge and sources of pollution, which were not taken into account before. The results obtained by the authors through statistical and spatial analysis of tritium content in groundwater during 2014-2017, indicate that currently within the territory of Kyiv there is a positive trend towards a slow gradual return of Cenomanian-Callovian groundwater complex to its natural state.